Prevalência de síndrome metabólica e fatores associados : um estudo de base populacional em Vitória/ES - Salaroli, Luciane Bresciani (2007)
Metabolic Syndrome (MS) can be defined as a complex disorder represented by a number of cardiovascular risk factors. This research aims at researching its prevalence and identifying its associated problems in Vitoria/ES, the data were collected from the project MONICA/WHO/Vitoria, which was carried out from 1999 to 2000. Socioeconomic, biochemical, anthropometric and hemodynamic parameters were collected among 1.663 individuals aged 25 to 64. The criteria used in diagnosing MS were the NCEP-ATP III and data collection were made according to appropriate parameters recommended for each procedure. Expected prevalence in Vitoria was of 26,9% (IC 95%: 26,6-27,1). Gender- related differences were insignificant. In the 25 to 34 age group, MS prevalence was of 15,7% and reached 48,4% among the 55-64 age group. There was a progressive increase of MS in women with higher socioeconomic level, when compared to women who belong to lower classes. The most frequent parameters observed in the subgroup of man were hypertension, hypertriglyceridemia, low HDL cholesterol levels, hyperglycemia and abdominal obesity. In the subgroup of women, hypertension was the most frequent symptom, followed by low HDL-c levels, abdominal obesity, hypertriglyceridemia and hyperglycemia. A high concentration of uric acid was identified as the variable predictor that contributed most for MS outcome, followed by body mass index (BMI) and age. However, in women, socioeconomic level was the first variable predictor. Calcium intake, as well as the percentage of appropriate diets, was lower in individuals with MS. It is possible to conclude that MS prevalence is also high in young individuals and that high blood pressure helps diagnosing it. Socioeconomic level was a crucial point related to MS incidence in women. It is important to control risk factors in a way to reduce diabetes incidence and cardiovascular illnesses in young people.